2013
DOI: 10.1523/jneurosci.4026-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic Contribution to Cortical Processing of Taste and Expectation

Abstract: Taste related information reaches the gustatory cortex (GC) through two routes: a thalamic and a limbic pathway. While evidence is accumulating on limbic-cortical interactions in taste, very little information is available on the function of the gustatory thalamus in shaping GC activity. Here we rely on behavioral electrophysiological techniques to study taste-evoked activity in GC before and after inactivation of the parvicellular portion of the ventroposteromedial nucleus of thalamus (VPMpc; i.e. the gustato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 46 publications
8
65
0
Order By: Relevance
“…Recent studies using rats have shown that neurons in the IC can change their firing in response to auditory cues anticipating the availability of taste (26,29,30). To determine whether IC activity could also be modulated by anticipatory cues in the present experimental conditions, we implanted 14 mice with movable bundles of 8 or 16 electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies using rats have shown that neurons in the IC can change their firing in response to auditory cues anticipating the availability of taste (26,29,30). To determine whether IC activity could also be modulated by anticipatory cues in the present experimental conditions, we implanted 14 mice with movable bundles of 8 or 16 electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple comparisons were corrected by controlling the false-discovery rate (Benjamini and Hochberg, 1995). To estimate the minimal number of neurons needed to reach a decoding accuracy of 95%, we created a large surrogate neuronal population from the available data (Rigotti et al, 2013). For each area, we considered the population of taste-selective units (based on the decoding procedure) and resampled the recorded neurons by randomly reassigning the labels of the spike responses to different tastes.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the recorded activity of a particular neuron in response to, respectively, S, N, C, and Q, was reassigned to the response of a new surrogate neuron to, respectively, Q, C, N, and S. This procedure was repeated for all 4! ϭ 24 possible permutations of the four taste labels, giving a neural population 24 times larger than the recorded one (for a more detailed description of the procedure, see Rigotti et al, 2013). We then proceeded with the same bootstrapped population decoding procedure as described above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations